THE REALITY OF THE CONCEPT OF THE FAMILY IN RELIGIOUS TEXTS (ON THE EXAMPLE OF THE WORK "THE HAPPY FAMILY" BY SHEIKH MUHAMMAD SODIQ MUHAMMAD YUSUF) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the content and significance of the concept of family in religious texts on the example of the work of Sheikh Muhammad Sadiq Muhammad Yusuf "Bakhtiyor Oila". The study highlights the role of the family in society and human life, views on marital relations and upbringing of children in Islamic sources. modern family relations.
Keywords: The concept of family, religious texts, Islamic values, happy family, couple relationships, child-rearing, spirituality, morality.